Coronary plaque characteristics associated with reduced thrombolysis in myocardial infarction flow in st-segment elevation myocardial infarction patients with plaque erosion. (25th November 2020) - Wang, J; Dai, J; Fang, C; Yu, B
Abstract: Background: It has been reported that the lumen factors of the culprit lesions are related to Thrombolysis in Myocardial Infarction (TIMI) flow grade in ST-Segment–Elevation Myocardial Infarction (STEMI) patients, but the factors of reduced TIMI flow in plaque erosion have not been studied. Methods: 329 STEMI patients with plaque erosion who underwent pre-intervention optical coherence tomography after thrombectomy were included and divided into 2 groups according to preprocedural TIMI flow grade [TIMI 0–1 (n=219) and TIMI 2–3 (n=110)]. Results: The patients with older age (55.7±11.1yrs vs. 51.8±10.6yrs, P=0.003) and diabetes patients (18.3% vs. 8.2%, P=0.015) had poorer TIMI flow, and the patients with reduced TIMI flow grade have lower initial cTnI (1.2ng/mL vs. 2.1ng/mL, P=0.023). The lesion in the LAD had better blood flow than the lesion in RCA (P=0.003), and the patients in TIMI 0–1 grade had more lipid plaques (53.9% vs. 41.8%, P=0.039), more macrophage (59.8% vs. 41.8%, P=0.002), and more calcification (34.2% vs. 21.8%, P=0.020). There was no statistically significant difference in the descriptive indicators of lipid or lumen between the two groups. And In a multivariate logistic regression model, the independent correlation factors of reduced TIMI flow grade in erosion patients were age, diabetes mellitus, lesion vessel, and macrophage. Conclusions: In STEMI patients with plaque erosion non-lumen factors greatly affect flow, which suggests that systemic treatment is as important as local treatment for plaque erosion. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Natural Science Foundation of China (81827806, 81801861), National Key R&D Program of China (2016YFC1301100)